Bignoniaceae endémicas del Perú - Granda, Arturo (2006)
The Bignoniaceae are represented in Peru by 47 genera and 166 species (Brako & Zarucchi, 1993), basically lianas and trees. Here we recognize four endemic species in the same number of genera. Three of these endemics grow in Mesoandean and Desert Shrubland regions, between 300 and 4000 m elevation, while the fourth is a liana in Very Humid Premontane Forests and Dry Forests regions. None of the species have been collected to date within Peru’s protected areas system.